Focus on bio-image informatics - Vos, Winnok H de; Munck, Sebastian; Timmermans, Jean-Pierre (Advances in anatomy, embryology and cell biology, 2016)
Seeing is believing – quantifying is convincing: Computational image analysis in biology -- Image degradation in microscopic images: Avoidance, artifacts and solutions -- Transforms and operators for directional bioimage analysis: A survey -- Analyzing protein clusters on the plasma membrane: Application of spatial statistical analysis methods on super-resolution microscopy images -- Image informatics strategies for deciphering neuronal connectivity -- Integrated high-content quantification of intracellular ROS levels and mitochondrial morphofunction -- KNIME for open-source BioImage analysis – A Tutorial -- Segmenting and tracking multiple dividing targets using ilastik -- Challenges and benchmarks in BioImage analysis -- BioImage informatics for big data.